Existence and uniqueness of positive solutions for a class of nonlinear fractional differential equations - Lingling Zhang; Huimin Tian (Advances in Difference Equations, 2017)
Abstract In the article, the existence and uniqueness of positive solutions for a class of fractional differential equation with nonlinear boundary conditions are discussed. By applying some fixed point theorems on cone, we gain a unique positive solution and construct two iterative sequences to approximate the solution. Moreover, as applications of our main results, some examples are also presented.